'Show Me Your Slugune and I'll Let You Have the Firstlook': Some Thoughts on Today's Digital Screenwriting Tools and Aprs. Issue 1 (November 2014) - Batty, Craig
Today's market is inundated with digital screenwriting tools and apps. From the introduction of formatting software that promised to give writers access to industry standard screenplay layout (Final Draft, Celtx) comes an era in which technologists are seeking to influence screenwriting practice itself (Scrivener, Slugline, Plotbot, StorySkeleton). Although perhaps not as explicit in their claims of success as the plethora of seminars by screenwriting 'gurus', digital tools and apps do in some ways promise a range of solutions to everyday screenwriting problems, at the very least by assuring users that they will help manage the logistics that often get in the way of creativity. But what do these digital interventions actually do? Do they shape creative practice, or merely provide tools to format a screenwriter's existing ideas? Do they help the writing process, or the processing of writing? This article examines some of the digital screenwriting tools and apps on the current market, and examines what they offer script development and writing practice. By reflecting on my own involvement in an online screenplay assessment platform, the article also suggests how embracing pedagogical aspects of screenwriting might give digital tools and apps the opportunity to help shape creative practice.